A Comprehensive Study on the Cytotoxic Action of Bioactive Compounds of Three Himalayan Herbs - Upadhyay, Gaurav; Sharma, Rajesh Kumar (Pharmacognosy Reviews)
Globally, Hepatocellular Carcinoma (HCC) is one of the main causes of cancer-related mortality generally affecting men more than women, and with an age of onset between late teens and 30s. Lamiaceae family also known as mint family containing aromatic flowering herbs. The potential of herbs in the Lamiaceae family, especially those indigenous to the Himalayan region has been brought to light by recent developments against HCC. Three such Himalayan herbs-Buggleweed (Ajuga bracteosa Wall. ex Benth), Wild marjoram (Origanum vulgare Linn.) and Ashy Roylea (Roylea elegans Wall.) along with their bioactive substances have cytotoxic effects on HCC are the subject of this review. These herbs are well-known for their abundant phytochemical makeup, which includes Essential Oils (EO’s), diterpenoids. phenolic acids, and flavonoids having strong anti-cancer properties. These include the capacity to regulate important cellular functions including apoptosis, cell cycle regulation, and angiogenesis, as well as antioxidant action, which is essential for preventing DNA damage brought on by oxidative stress. These herbs are very appealing for the prevention and treatment of HCC because of their capacity to increase the activity of liver detoxifying enzymes and guard against liver fibrosis. These plants are a great source of possible therapeutic agents for the prevention and treatment of hepatocellular carcinoma because of their widespread availability and diverse chemical makeup. Incorporating these plant-based substances into existing treatment plans may offer a more comprehensive and economical strategy for battling this debilitating illness.
Keywords: Hepatocellular carcinoma; Himalayan herbs; Lamiaceae family; Cytotoxic action; Bioactive compounds; Therapeutic potential; Apoptosis